Spiritualitas Mengurangi Kesepian Lansia pada Era New Normal Di Wilayah Kerja Puskesmas Pauh Kota Padang - Muthmainnah, Muthmainnah; Sumarsih, Gusti; Andrifa, Sri Dinda (REAL in Nursing Journal, 2023)
Background: Elderly people experience physical and psychological changes. Loneliness is one of the psychological disorders experienced by elderly people. Spiritual well-being can overcome loneliness. Since Covid-19, the elderly has become increasing lonely due to limitations in social interaction. This is the aim of the study to determine the correlation between spiritual well-being and loneliness of elderly people in the new normal era at the Public Health Centre Pauh, Padang, Indonesia. Methods: Cross-sectional analytical was used in this study. Participants were elderly in Public Health Centre Pauh (N=94). This study used the University of California Los Angeles (UCLA) Loneliness Scale and Spiritual Well Being Scale (SWBS) as its instrument. Samples were taken with purposive sampling. Results: The results showed that low spiritual was 22.3% and the spiritual high was 77.7%. Seniors who did not experience loneliness were 26.6%, loneliness was low at 59.6%, loneliness was medium at 11.7% and those who experienced severe loneliness were 2.1%. There is a correlation between spirituality with a level of elderly loneliness (p=0.000; α=0.05). The study of the bivariate analysis showed that low loneliness is based on 3 points in UCLA and high spirituality is based on God’s love and caring, satisfaction, and happiness. Conclusion: Based on the result, doing other research is needed, nurse suggest integrating spiritual care with usual care in Health Public Centre.Keywords: Caring, Elderly, Loneliness, Spiritual